2019
DOI: 10.1186/s13058-019-1143-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of pathogenic germline variants in BRCA1, BRCA2, PALB2, CHEK2 and TP53 in ductal carcinoma in situ diagnosed in women under the age of 50 years

Abstract: Introduction Ductal carcinoma in situ (DCIS) is a non-obligate precursor of invasive ductal breast cancer, and approximately 20% of screen-detected tumours are pure DCIS. Most risk factors for breast cancer have similar associations with DCIS and IDC; however, there is limited data on the prevalence of the known high and moderate penetrance breast cancer predisposition genes in DCIS and which women with DCIS should be referred for genetic screening. The aim of this study was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
(41 reference statements)
1
13
1
Order By: Relevance
“…Observed frequencies of these mutations are not inconsistent with those in the general population. For example, the frequency of BRCA1 pathogenic variants in healthy non-Finnish European controls in gnomAD is 0.38% (81 of 21,384) compared to 0.25% in our cohort 23 .…”
Section: Discussioncontrasting
confidence: 65%
“…Observed frequencies of these mutations are not inconsistent with those in the general population. For example, the frequency of BRCA1 pathogenic variants in healthy non-Finnish European controls in gnomAD is 0.38% (81 of 21,384) compared to 0.25% in our cohort 23 .…”
Section: Discussioncontrasting
confidence: 65%
“…Similar genetic variants have been shown to predispose to increased risk of both in situ and invasive breast cancer [26]. A study among Japanese women found a similar prevalence of high penetrance BRCA1/2 variants in women with invasive and breast carcinoma in situ [27].…”
Section: Discussionmentioning
confidence: 78%
“…In patients with nonclonally related recurrences, the major question is what factors constituted the basis of risk in these women who developed two clonally different cancers in the same breast over time. We can speculate that such cases may be due to genetic predisposition as there is clear evidence that the known invasive breast cancer predisposition genes and polymorphisms also predispose to DCIS, particularly ER+ DCIS 16 , 17 . However, the limited data on rare germline variants in this study does not support this theory.…”
Section: Discussionmentioning
confidence: 99%